Bibliostyle : how we live at home with books - Freudenberger, Nina; Stein, Sadie (Clarkson Potter/Publishers, 2019)
Interior designer Nina Freudenberger, New Yorker writer Sadie Stein, and Architectural Digest photographer Shade Degges give readers a peek at the private libraries and bookshelves of passionate readers all over the world, including Larry McMurtry, Silvia Whitman of Shakespeare and Co., Gay and Nan Talese, and Emma Straub. Throughout, gorgeous photographs of rooms with rare collections, floor-to-ceiling shelves, and stacks upon stacks of books inspire readers to live better with their own collections. -- amazon.com